Promoting Academic Competence in School Adolescents: Results of 15-day Life Style Intervention Programme - Singh, Arun Pratap; Misra, Girishwar (INDIAN EDUCATIONAL REVIEW, 2011)
There has been paucity of theory-based life style interventions to improve academic competence among school adolescents. Therefore, present study examined the effect of Life Style Intervention Programme (LSIP) introduced through a psycho-education programme on academic competence in a sample (N = 100) of students in a residential school located at Mankapur, Gonda in Uttar Pradesh, India. Academic competence (AC) was evaluated through a self-report measure. The results indicated that adolescents who participated in a 15-day LSIP reported of increased AC. Also, some of the aspects significant for academic performance (i.e., self-esteem, anxiety, depression, optimism) as secondary outcomes were also assessed. The findings have implications for life style education efforts in schools, which could have a major impact on the academic performance of students.